Literature Review: The Influence of Learning Styles on Student Achievement - T. M. Jamil; Azwar Azwar; Eka Nurmala (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2025)
Student achievement is a crucial indicator for evaluating the effectiveness of the learning process in educational institutions. Variations in students’ academic performance indicate the influence of multiple internal and external factors, one of which is learning style. Learning style refers to an individual’s tendency in receiving, processing, and understanding information during the learning process. This article aims to comprehensively review the influence of learning styles on student achievement through a literature review approach. The method employed involves an in-depth analysis of textbooks, national and international journal articles, and relevant research reports addressing learning styles and academic achievement. The selected literature was analyzed using content analysis techniques to identify patterns, similarities, and differences in research findings. The results of the review indicate that learning styles are related to student achievement, although the degree of influence varies depending on educational level, subject characteristics, and instructional approaches. Visual, auditory, and kinesthetic learning styles demonstrate different contributions to academic performance, particularly when instructional methods align with students’ learning preferences. However, the findings also reveal that learning style is not the sole determinant of student achievement. Other factors such as learning motivation, learning strategies, instructional quality, and learning environment play significant roles. Therefore, learning styles should be understood proportionally as one of several considerations in designing effective and inclusive instruction. This article recommends a holistic learning approach that not only accommodates diverse learning styles but also fosters students’ adaptability and independent learning skills to enhance academic achievement sustainably.